Effects of Wu Qin Xi exercise on reactive inhibition in Parkinson’s disease: A randomized controlled clinical trial - Wang, Zhen; Pi, Yanling; Tan, Xiaoyin; Wang, Zhen; Chen, Robert; Liu, Yu; Guo, Wei; Zhang, Jian (Frontiers in Aging Neuroscience, 2022)
Objective: Motor symptom in patients with Parkinson’s disease (PD) are related to reduced motor inhibitory ability (proactive and reactive inhibition). Although exercise has been shown to improve this ability, its effects on different levels of motor inhibition have not been determined. Methods: 60 patients with PD aged 55–75 years were allocated randomly to 24-week exercise interventions [Wu Qin Xi exercise (WQX) and stretching exercise (SE)]. The stop signal task and questionnaires were administered pre and post interventions. 25 age-matched healthy controls were recruited to obtain reference values for inhibition. Results: Compared to healthy controls, patients with PD showed motor inhibition deficits in reactive inhibition, but not in proactive inhibition. Post-intervention, the WQX group showed significant improvement in reactive inhibition compared to the SE group. In both the WQX and SE groups, movement speed was improved post-intervention, accompanied by reduction in negative emotions, stable improvement of sleep quality, and high self-reported satisfaction levels. Conclusion: This study demonstrated that Wu Qin Xi exercise can improve the reactive inhibition of patients with PD. Our results provide theoretical support for the formulation of reasonable and effective exercise prescriptions for PD rehabilitation. Clinical Trial Registration: This study has been registered in the Chinese Clinical Trial Registry (ChiCTR2000038517, 18 January 2021). Keywords: Parkinson’s Disease, Reactive Inhibition, Proactive Inhibition, Physical Exercise, Stop Signal.